APTUS — THE EXPERIENCE OF AN INSTITUTION - Bento, Rita (2020)
Introduction: Type I Endoleak (EL1) is often associated with a high risk of aneurysmal expansion and consequent secondary rupture. The Heli-FX EndoAnchor system (Aptus Endosystems®) has emerged as an alternative for the treatment of EL1, whose mechanism consists of "anchoring" or "screwing" the prosthesis to the aortic wall in order to obtain better apposition /sealing. Objectives: The main objective of this study was to analyze the initial routine clinical experience of EndoAnchor's use in a tertiary institution and assess safety/effectiveness of its use. Methods: We selected all cases in which Endoanchors were applied since this technology was available in our Institution. We analyze the main indications as well as the outcomes of its use. Results: Since March 2017 until March 2019 (24 months), 12 patients underwent Endoanchors fixation. Endoanchors were implanted in 8 patients (66%) at the time of an initial EVAR procedure (primary use) and in 4 patients (33%) with an existing endograft and proximal aortic neck complications (secondary use). Regarding the primary use of Endoanchors, in 5 patients (62.5%) the indication was prophylactic due hostile aortic neck anatomy and in 3 patients (37.5%) the indication was early EL1, (75% elective cases and 25% urgent cases). Endoanchors were used in secondary procedures in 4 patients, in 3 cases (75%) the indication was late EL1 and in 1 case (25%) it was for REVAR, (50% elective cases and 50% urgent cases). In all cases, our institution presented a 100% technical success and 0% morbimortality in 30 days. There were no residual EL1 at the end of the procedure in angiography. During an average follow-up of 16.0 ± 7.7 months, no secundary procedures were perfomed, no related deaths to aneurysmal pathology or aneurysm ruptures were observed. Conclusion: From the experience of our institution, Endoanchors were used prophylactically in EVAR cases with hostile aortic anatomy and are a treatment option in EL1, with and without rupture with promising results.